Minerals, Nutrients and Active Compounds of Rambutan Fruits - Sukemi - (PROSIDING SEMINAR KIMIA, 2015)
The main objective of this essay was to describe the minerals, nutrients and active compounds of rambutan (Nepheliumlappaceum L.) fruits. Flesh fruit of rambutanis a sourceof minerals and ascorbic acid that are needed by human. Its seed oil provides mineral and fatty acid. Its peel contains ellagic acid, corilagin and geraniin that have biological activities, such as antioxidant, anticancer, anti-inflammation, anti-hyperalgesic antiviral, anti-semicarbazide-sensitive amine oxidase (SSAO), and anti-hypertensive. Rambutan is not only consumed as fresh fruits, but also it can be used as sources of food and medicine products.